Beyond Oxides: Nitride as a Ligand in a Neutral IrIXNO3 Molecule Bearing a Transition Metal at High Oxidation State. Issue 44 (1st July 2019) - Wolański, Łukasz; Domański, Mateusz; Grochala, Wojciech; Szarek, Paweł
Abstract: Theoretical calculations utilizing relativistic ZORA Hamiltonian point to the conceivable existence of an IrNO3 molecule in C 3 v geometry. This minimum is shown to correspond to genuine nonavalent iridium nitride trioxide, which is a neutral analogue of cationic [IrO4 ] + species detected recently. Despite the presence of nitride anion, the molecule is protected by substantial barriers exceeding 200 kJ mol −1 against transformations leading, for example, to global minimum (O=)2 Ir−NO, which contains metal at a lower formal oxidation state. Abstract : A new color in the rainbow of iridium compounds? A theoretical study suggests that, despite the presence of nitride ligand, IrNO3 might be prepared in the form of iridium(IX) nitride trioxide rather than iridium(I) nitrate(V). Distorted tetrahedral IrNO3 would be an unprecedented neutral molecule which contains high‐valent Ir IX .